Guarding the viruses away: Gardu and the pandemic reflections in Yogyakarta - Fahroji, Fahmi Rizki; Pratama, Adrianus Venda (Universitas Padjadjaran, 2024)
Historical narratives highlight the gardu, a bamboo gateway structure, as a traditional Javanese technology for neighborhood security. During the initial three months of the COVID-19 pandemic, a resurgence of gardu construction was observed in Yogyakarta as communities adapted this cultural practice to shield themselves from the virus. These structures became a means of mitigating both the pandemic’s spread and the accompanying flood of panic-inducing rumors. Communities increasingly viewed outsiders as potential virus carriers, often metaphorically equating them to thieves or malevolent forces threatening their safety. This paper explores the community’s experience in responding to the coronavirus crisis through the immediate construction of gardu in urban housing complexes. It examines how moral panic shaped community perceptions and actions, such as the erection of these structures to create physical and symbolic barriers against outsiders. Also, this study explore the community perception of gardu after the pandemic. Ethnographic research, including observations and interviews, was conducted in two gated hamlets in Yogyakarta. Additional data were sourced from prior studies on community responses to pandemics, with a focus on experiences from 2020, and their current perception of gardu after the pandemic. This study seeks to analyze gardu as a local, culturally embedded form of lockdown, assessing its effectiveness from an anthropological perspective. It also aims to reflect on the ways in which pandemic situations disrupt community behaviors and to draw lessons for future crisis preparedness; as well as decribe the community changing perception towards gardu and the post pandemic situation.